2020
DOI: 10.20961/ijie.v4i1.44727
|View full text |Cite
|
Sign up to set email alerts
|

Combining Flipped Classroom and Mind Mapping in Indonesian Vocational Schools: Their Influence to Students’ Critical Thinking Ability

Abstract: <span lang="EN-US">The main problem of students in solving problems is the low ability to think. This study aims to improve students' critical thinking skills and measure the effectiveness of the combination of flipped classroom learning models and mind mapping. This research method used is a quantitative approach with a quasi-experimental design. The sample from this study was 31 students from the experiment class and 31 students from the control class. Data collection is done through critical thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…his research is descriptive research by applying a qualitative approach. According to Moleong (2018), descriptive qualitative research is a research method that aims to understand an event or experience from the participant's point of view. This research uses qualitative data to reveal the meaning and participants' interpretations of these events or experiences.…”
Section: Methodsmentioning
confidence: 99%
“…his research is descriptive research by applying a qualitative approach. According to Moleong (2018), descriptive qualitative research is a research method that aims to understand an event or experience from the participant's point of view. This research uses qualitative data to reveal the meaning and participants' interpretations of these events or experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Some in-class activities that can be carried out are discussions and reviews of materials considered difficult for students. Besides discussions, there are problem-solving activities (Usmadi and Ergusni, 2019), pair practice (Sumardi et al, 2020), doing exercises with a higher level of difficulty (Fahmi et al, 2020), making mind maps (Nugroho et al, 2020), and designing projects or making products to exhibitions (Basyah, 2018). Therefore, it can be concluded that the flipped classroom can be combined with other learning models with thorough preparation, both in designing in-class learning and out-ofclass learning.…”
Section: The Implementation Of Flipped Classroommentioning
confidence: 99%
“…In the 21st century, quality improvement in various aspects of life is getting higher. The development of science and technology encourages every nation to exert its mind and all its resources (Nugroho et al, 2020). Getting an education is one approach to learning new things.…”
Section: Introductionmentioning
confidence: 99%